Receivables Management in Reducing the Risk of Uncollectible Receivables at Bank Syariah Indonesia (BSI) Bengkalis Branch - Nurul Hastika; Husni Mubarak (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze receivables management in reducing the risk of uncollectible receivables at Bank Syariah Indonesia (BSI) Bengkalis Branch. The focus of the research includes the types of financing that have the potential to cause uncollectible receivables, the factors that cause non-performing receivables, and the strategies or efforts made by BSI in minimizing the risk of uncollectible receivables. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation related to the receivables management process and the handling of problematic receivables. The results of the study show that the types of financing that have the most potential to cause uncollectible receivables are financing based on murabahah, ijarah, and istishna' contracts. The main factors causing the occurrence of non-performing receivables come from the weakness of customer feasibility analysis, lack of optimal post-financing monitoring, and unstable customer economic conditions. BSI Bengkalis Branch has implemented a risk mitigation strategy through the implementation of the 5C principle, periodic receivables monitoring system, financing restructuring, and financial education to customers. The conclusion of this study shows that the receivables management at BSI Bengkalis Branch has been running quite well, but it still needs to be improved through strengthening supervision, digitizing receivables monitoring, and improving the quality of initial financing analysis so that the risk of uncollectible receivables can be minimized more effectively and sustainably.